The information needs of female Police Officers involved in undercover prostitution work - Lynda M. Baker (Information Research: An International Electronic Journal)
The purpose of this study was to examine the information behavior of female police officers involved in undercover prostitution work. Seven Vice Officers were interviewed during the summer of 2003 and two were observed during one decoy operation. The model, Information Seeking of Professionals, provided the framework for understanding their needs within the context of their role as decoys. The results revealed that the officers need a variety of information and start seeking it before they transfer to the Vice Unit. Their work demands the use several methods of informal communication, including signals and dress code. Information sources include the men who solicit their services, the female sex workers with whom they share space, members of the community, and their fellow officers who are responsible for protecting their lives.